Evaluación de las estrategias competitivas y sociodemográficas cámara de comercio de Facatativá (2020)
This original reflection article, shows the importance given with the realization of sociodemographic studies in a region since they can be measured thanks to the characterization of the population in aspects of education, housing, health and safety in order to be able to diagnose the current state of socioeconomic development in the territory, this is how the Facatativá Chamber of Commerce -CCF through the development of internships of students of the University of Cundinamarca and professional staff of the same, carried out the Sociodemographic characterization in the municipalities of the jurisdiction, as a result of the internship the technical report was focused on the research and analysis of the strategies that were implemented to strengthen and / or enhance the socio-regional development based on the analysis of data obtained in the study implemented by the Chamber of Commerce and the application of a survey of 3 experts of the entity based on the theoretical variables competitive strategies and nationalized study municipalities of the jurisdiction of the Facatativá Chamber of Commerce.